2018
DOI: 10.1038/s41598-018-33367-1
|View full text |Cite
|
Sign up to set email alerts
|

Baseline resistance-guided therapy does not enhance the response to interferon-free treatment of HCV infection in real life

Abstract: Hepatitis C virus (HCV) response to direct-acting antivirals (DAAs) may be influenced by the presence of resistance-associated substitutions (RASs). This study aimed to assess if NS5A baseline RAS-guided treatment enhances the rate of sustained viral response (SVR) in naïve HCV-infected patients in clinical practice. All HCV-infected patients who initiated treatment with interferon (IFN)-free DAA-based regimens between March 2016 and May 2017 in 17 Spanish hospitals and who had evaluable SVR 12 weeks (SVR12) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…Although we included patients with <800 000 IU/mL (for whom RAS testing is not recommended), SVR rates were comparable to previous data from clinical and real‐world studies 6,7,13,14,23 . All other regimens with an 8‐ to 12‐week duration were also highly effective with SVR rates of ≥97%, which agrees with other reports 3,26‐29 . In patients with baseline NS5A RASs who were treated according to the guidelines, the overall SVR rate was still 95%.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Although we included patients with <800 000 IU/mL (for whom RAS testing is not recommended), SVR rates were comparable to previous data from clinical and real‐world studies 6,7,13,14,23 . All other regimens with an 8‐ to 12‐week duration were also highly effective with SVR rates of ≥97%, which agrees with other reports 3,26‐29 . In patients with baseline NS5A RASs who were treated according to the guidelines, the overall SVR rate was still 95%.…”
Section: Discussionsupporting
confidence: 83%
“…6,7,13,14,23 All other regimens with an 8-to 12-week duration were also highly effective with SVR rates of ≥97%, which agrees with other reports. 3,[26][27][28][29] In patients with baseline NS5A RASs who were treated according to the guidelines, the overall SVR rate was still 95%. Overall, the SVR rates for the individual regimens in patients with and without baseline NS5A RASs varied only slightly and the differences were not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of naturally‐occurring baseline RASs in NS5B and mostly in NS5A has been assessed in several studies and also can influence treatment outcome . However, current studies have suggested that routine testing of baseline RASs in naïve HCV‐infected patients does not improve the SVR rate or have a minimal (1%‐3%) effect on patient responses . For this reason, recommendations for testing baseline RAS are contradictory.…”
Section: Discussionmentioning
confidence: 99%